Inovação científica em estudos medievais: descobrindo os sons do português arcaico - Massini-Cagliari, Gladis [UNESP] (2013)
In the context of the confrontation between the several existing possibilities of comprehension of the term “innovation” in the Linguistic fields, the main goal of this paper is to explore the comprehension of this term considering the adoption of new methodologies, based on the analysis of a specific case, of the Research Group Phonology of Portuguese: Archaic and Brazilian periods, which investigates the phonology of a past period of the language from which there are no more alive native speakers.